Biophenol extracts from olive oil mill wastewaters by membrane separation and adsorption resin. (29th July 2016) - Savarese, Maria; De Marco, Elena; Falco, Salvatore; D'Antuoni, Isabella; Sacchi, Raffaele
Summary: The disposal of olive oil mill wastewater, the main effluent resulting from the production of olive oil, presents technical difficulties which are still unsolved. Several techniques have been proposed for the treatment of this effluent, but only a few processes have been applied at pilot or industrial scale and, nowadays, the management of olive oil mill wastewaters represents an environmental problem in the olive oil‐producing countries. Tests were carried out at pilot scale, by means of a plant with 1 m 3  h −1 capacity; a process for the treatment and valorisation of olive mill wastewaters was reported. By this process, it was possible to produce starting from olive mill wastewaters resulting from a three‐phase milling system, 62% of purified water, which could be reused in the industrial processes, and a concentrated phenolic extract (9.5% total phenols), which could be used in food, cosmetic or animal feed industry. Abstract : Aim of the OMWW treatment proposed.